Proceedings of the 8th Annual IEEE/ACM International Symposium on Code Generation and Optimization 2010
DOI: 10.1145/1772954.1772993
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic interpretation for dynamic scripting languages

Abstract: Dynamic scripting languages offer programmers increased flexibility by allowing properties of programs to be defined at run-time. Typically, program execution begins with an interpreter where type checks are implemented using conditional statements. Recent JIT compilers have begun removing run-time checks by specializing native code to program properties discovered at JIT time.This paper presents a novel intermediate representation for scripting languages that explicitly encodes types of variables. The dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The CLBG benchmark solutions have already been used for validation purpose by several research works. Among other examples, CLGB was used to study dynamic behavior of non-Java JVM languages [20], to analyze dynamic scripting languages [36] and compiler optimizations [34], or even to benchmark a JIT compiler for PHP [16]. At the best of our knowledge, CLGB was only used once for energy consumption analysis.…”
Section: Related Workmentioning
confidence: 99%
“…The CLBG benchmark solutions have already been used for validation purpose by several research works. Among other examples, CLGB was used to study dynamic behavior of non-Java JVM languages [20], to analyze dynamic scripting languages [36] and compiler optimizations [34], or even to benchmark a JIT compiler for PHP [16]. At the best of our knowledge, CLGB was only used once for energy consumption analysis.…”
Section: Related Workmentioning
confidence: 99%
“…Dynamic instruction frequencies and basic block hotness are the fundamental metrics that are used in tracing-based compilation approaches. These metrics are also used in the work by Williams et al [24], where the authors propose specializing native code to program properties found at JIT-compilation time, thus improving the overall program execution time.…”
Section: Related Workmentioning
confidence: 99%
“…The CLBG includes solutions for thirteen different problems, written in twenty eight different programming languages. These benchmarks have been used in several research works, to study the dynamic behavior of non-Java JVM languages [15], to analyze dynamic scripting languages [32] and compiler optimizations [30], to benchmark a JIT compiler for PHP [11], and in the design of the R language [20]. In fact, the repository of programs included in CLBG are also particularly suitable to analyze the energy efficiency of programming languages due to the following characteristics:…”
Section: Computer Language Benchmark Gamementioning
confidence: 99%